Development of diabetes register in low-mid income country: survey of healthcare professionals’ behavioural change wheel - Igumbor, Eunice O.; Agofure, Otovwe; Oshionwu, Echinei J.; Bwititi, Phillip T.; Nwose, Ezekiel U. (International Journal Of Community Medicine And Public Health, 2019)
Background: There has been and ongoing research and development on diabetes care in Ndokwa community of Nigeria, and one of the items to be addressed is development of diabetes register in some of the health facilities. This study assesses the behavioural change wheel of the healthcare professionals to address the willingness of the primary healthcare providers willing to scale up and sustain the diabetes register; and how glycaemic control and metabolic syndrome factors in diabetes patients were assessed. Methods: The study adopted clinical observational approach and survey questionnaires. A descriptive cross sectional method evaluated how glycaemic control among diabetes patients (n=42) was assessed. Clinical observations were at Catholic Hospital Abbi, while the survey of healthcare professionals (n=71) included health facilities in other communities. Data from questionnaire and test results was analysed using Microsoft Excel Data Analysis Toolpak 2010. Results: It is observed that 62% wished they had a diabetes register. Over 50% of the patients showed presence of >2 metabolic syndrome indices. Further, ≈52% disagreed that diet, exercise, medication, quitting smoking and less stress contributed to effective control and management of diabetes. Conclusions: Most of the respondents thought that their practice did not have a special interest in diabetes. There is prevalence of metabolic syndrome, but the majority of healthcare professionals did not view lifestyle as effective to control diabetes. These observations highlight the need for diabetic education on healthcare professionals and patients.